The Influence of Transformational Leadership and Work Culture on Work Commitment and Its Implications on the Performance of Village Fund Managers: (Survey in Several Districts on Flores Island, East Nusa Tenggara Province) - Agustina Mogi; Sidik Priadana; Ester Manik (Quantitative Economics and Management Studies, 2024)
This research examines the influence of transformational leadership and work culture on work commitment and its implications for the performance of village fund managers on Flores Island, East Nusa Tenggara. The research method used is quantitative research with an explanatory survey approach. Data was collected through interviews, observation, and questionnaires with a Likert scale. Respondents are village fund managers from 6 districts on Flores Island. Hypothesis testing was done using Structural Equation Modeling (SEM) with SmartPLS 3.00 software. The research results show that transformational leadership and work culture significantly influence the work commitment and performance of village fund managers. Strong transformational leadership, characterized by collaboration, honesty, and trust, encourages increased work commitment and performance of village fund managers. Meanwhile, a positive work culture based on integrity, honesty, and accountability contributes to work commitment and performance. High work commitment also positively impacts individual and group performance, increasing motivation, job satisfaction, and the ability to face challenges. Finally, improving the performance of village fund managers on Flores Island requires the development of transformational solid leadership, the formation of a positive work culture based on the values of integrity and accountability, and increasing the work commitment of individual village fund managers. It is hoped that the results of this research can improve the effectiveness of village fund management and services to the community.